2018
DOI: 10.5505/tjtes.2018.94572
|View full text |Cite
|
Sign up to set email alerts
|

Admission Neutrophile to Lymphocyte Ratio and Postoperative Mortality in Elderly Hip Fracture Patients

Abstract: BACKGROUND: Hip fractures in elderly patients are associated with a high mortality rate. Most deaths associated with hip fracture result from complications after surgery. Recent studies suggest that the neutrophil-to-lymphocyte ratio (NLR), which is a laboratory marker used to evaluate systemic inflammation, may be useful to estimate excess mortality. This study aimed to investigate the prognostic value of admission NLR in elderly patients with hip fracture. METHODS: We evaluated patients admitted to the Ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 14 publications
1
38
1
Order By: Relevance
“…Forget et al reported that in addition to advanced age, male gender, and comorbid diseases, a postoperative 5th day NLR value >5 following hip fracture surgery was associated with high postoperative mortality risk [3]. Temiz and Ersözlü stated that postoperative NLR ≥4.7 increased the risk of mortality in patients with hip fracture [5]. In our study, NLR was similar between discharged and deceased patients at the preoperative period.…”
Section: Discussionsupporting
confidence: 65%
“…Forget et al reported that in addition to advanced age, male gender, and comorbid diseases, a postoperative 5th day NLR value >5 following hip fracture surgery was associated with high postoperative mortality risk [3]. Temiz and Ersözlü stated that postoperative NLR ≥4.7 increased the risk of mortality in patients with hip fracture [5]. In our study, NLR was similar between discharged and deceased patients at the preoperative period.…”
Section: Discussionsupporting
confidence: 65%
“…In prior publications, laboratory evaluation results, including admission hemoglobin concentration, blood level of albumin, and Neutrophil to lymphocyte ratio (NLR), were found to be significantly related to 30-day or 1-year mortality in patients with a hip fracture [ 3 , 16 , 17 , 18 , 26 , 29 ]. Our results showed that an admission hemoglobin concentration of <10 g/dL was a significant predictor of mortality, a finding in concordance with those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, including age, gender, physical status, institutionalization, comorbidities, findings of laboratory evaluations, method of treatment, and time to surgery have been reported to be associated with in-hospital, 30-day, and 1-year mortality after a hip fracture in diverse populations and countries [ 3 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In Thailand, data from Chiang Mai University show factors correlated with mortality after hip fracture in the periods 1997 through 1998, 1998 through 2003, and 2006 through 2007 including male gender, greater age, nonoperative treatment, surgical treatment delayed more than a week, chronic illnesses, poor pre-fracture walking ability, and absence of medical treatment for osteoporosis [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations